Hubungan Indek Masa Tubuh (BMI) dan Siklus Menstruasi Terhadap Kejadian Anemia Pada Remaja - Hindratni, Findy; Susilawati, Elly; Martin, Refi Filiana (JURNAL IBU DAN ANAK, 2022)
pregnant women. Anemia is 10 times more likely to occur in girls than boys. Young women are more at risk because every month they experience menstruation and are in a period of growth that requires more iron intake.Based on data from the Ministry of Health, 6.41% of adolescent girls in Riau Province are anemic. The purpose of this study was to determine the relationship between body mass index (BMI) and the menstrual cycle on the incidence of anemia in adolescent girls. This type of research is quantitative analytic with a cross sectional approach. The study was conducted in January-April 2022. The population was 105 adolescent women at PPM Al-Hidayah in 2022 with a total of 83 samples. Data processing used chi square. The results showed that there was a relationship between body mass index (BMI) and the incidence of anemia in adolescent girls, the chi square test value p = 0.023 so that p value <0.05 then H0 was rejected, and there was no relationship between the menstrual cycle and the incidence of anemia in adolescents women, chi square test value p = 0.329. It is recommended to the school to provide counseling about nutritional status because adolescent women with normal or abnormal nutritional status have the potential to experience anemia, so they can provide counseling about the importance of consuming animal protein and iron intake in adolescents